2008
DOI: 10.1073/pnas.0802753105
|View full text |Cite
|
Sign up to set email alerts
|

Preprocalcitonin signal peptide generates a cytotoxic T lymphocyte-defined tumor epitope processed by a proteasome-independent pathway

Abstract: We identified an antigen recognized on a human non-small-cell lung carcinoma by a cytotoxic T lymphocyte clone derived from autologous tumor-infiltrating lymphocytes. The antigenic peptide is presented by HLA-A2 and is encoded by the CALCA gene, which codes for calcitonin and for the ␣-calcitonin gene-related peptide. The peptide is derived from the carboxy-terminal region of the preprocalcitonin signal peptide and is processed independently of proteasomes and the transporter associated with antigen processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 42 publications
0
86
0
Order By: Relevance
“…ϩ T cell epitopes resides in the signal peptide, as described previously for other secreted tumor antigens (17)(18)(19). These findings suggest that MDK may be novel candidate for the development of a cancer vaccine.…”
Section: Midkine (Mdk)mentioning
confidence: 69%
See 1 more Smart Citation
“…ϩ T cell epitopes resides in the signal peptide, as described previously for other secreted tumor antigens (17)(18)(19). These findings suggest that MDK may be novel candidate for the development of a cancer vaccine.…”
Section: Midkine (Mdk)mentioning
confidence: 69%
“…ϩ T cell epitopes, as has been found for numerous tumor and viral antigens (17)(18)(19). Again, the presence of several hydrophobic residues in signal peptides favors their binding to HLA-A2 (33).…”
Section: Discussionmentioning
confidence: 93%
“…In a parallel study, a proteasome-and TAPindependent tumor antigen from the signal sequence of the preprocalcitonin protein (ppCT [16][17][18][19][20][21][22][23][24][25] ) was found to represent a human TEIPP, in that this HLA-A2 presented peptide was selectively presented by tumor cells with TAP deficiency [54]. This peptide is liberated in the ER lumen by sequential cleavage with SP and SPP [55] and is a clear example of the alternative TAP-independent peptide repertoire.We emphasize that not all TAP-independent peptides fail to be presented by processing intact cells. Mass spectrometry analyses have revealed that part of this repertoire can be detected on the surface of TAP-proficient cells [25][26][27].…”
mentioning
confidence: 99%
“…Our data provides one example since we were able to more readily detect and expand CTL specific for the KLK4A epitope compared to other HLA-A*0201-restricted peptides such as PSA 154-163 , PAP 299-307 and KLK4B,D,E that are located in their respective core proteins. In support of this theory, HLA-A*0201-restricted immunogenic epitopes have been identified within the signal peptides of other human TAA, including the melanoma antigen tyrosinase [32][33] and the medullary thyroid and lung carcinoma associated CALCA gene [31]. Notably, a HLA-A*0201-restricted epitope is located within the signal sequence of MUC1…”
Section: Discussionmentioning
confidence: 68%
“…The location of the epitope within the signal sequence may explain why KLK4A-specific CTL responses were readily induced in both healthy donors and prostate cancer patients. Signal peptide molecules are known to associate with HLA-A*0201 molecules [29][30] and their capacity to induce CTL has been documented in a few cases [31][32][33][34][39][40]. Epitopes derived from signal peptides can be directly processed and presented on MHC Class I when expressed endogenously by tumor cells or DC (direct presentation) [40].…”
Section: Discussionmentioning
confidence: 99%